Contributing to the Future of Climate Action: CGIAR's Participation at COP29 in Baku - CGIAR Climate Impact Platform (CGIAR System Organization, 2024)
The UNFCCC 29th Conference of the Parties will be held from November 11 to 22, 2024, in Baku, Azerbaijan. Focused on advancing the goals of the United Nations Framework Convention on Climate Change (UNFCCC) and the Paris Agreement, the 29th Conference of Parties (COP29), will discuss the efforts to limit global warming, adapt to the impacts of climate change, and mobilize financing for these activities.